REPRESENTASI CITRA PEREMPUAN PADA ANTOLOGI CERPEN PEREMPUAN-PEREMPUAN PEMENANG KARYA RAHMAT JABARIL - Hidayati, Nila; Kadaryati; Sholeh, Khabib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the representation of women's images in the short story anthology "Women-Winners" by Rahmat Jabaril. A qualitative approach with descriptive methods was used in this study. The object of this study was the short story anthology "Women-Winners" by Rahmat Jabaril, published in 2022. The research data consisted of quotes, phrases, sentences, and paragraphs depicting women's images. Data collection techniques were carried out using reading and note-taking techniques. The research instrument was the researcher herself with the aid of data recording cards. Data analysis was carried out through data collection, data reduction, data presentation, and drawing conclusions. The results of the analysis were presented using informal methods. The results showed that the representation of women's images is divided into two main aspects: self-image and social image. Women's self-image encompasses physical and psychological aspects. The physical aspect is shown through biological conditions, body changes due to activity, and physical aging. The psychological aspect depicts women as persistent, independent, responsible, able to accept the realities of life, but also experiencing mental stress and limitations in making life choices. Meanwhile, women's social image encompasses women's roles in the family and society. Within the family, women are portrayed as wives who maintain household harmony, loving mothers, and hardworking figures who provide for their families. In society, women are portrayed as active, independent, and productive individuals capable of contributing to the economy, yet they still face objectification and vulnerability in public spaces.